2017
DOI: 10.1007/s11356-017-9564-6
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of staphylococcal enterotoxin A by genetic engineering technology and determination of staphylococcal enterotoxin A in water by HPLC-ESI-TOF

Abstract: Staphylococcal enterotoxin A (SEA) was the major virulence factor of Staphylococcus aureus and a biomarker of S. aureus. To establish a fast, low cost, high accuracy, reliable, and simple method for detecting S. aureus, SEA was analyzed by HPLC-ESI-TOF. SEA was not yet commercially available in universal, so SEA was prepared before it was analyzed by HPLC-ESI-TOF. The result showed that high purified SEA was successfully prepared and SEA has normal distribution in mass spectra. A large amount of recombinant SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Preparation of SEA toxin protein was completed by Escherichia coli expression system and Ni-NTA affinity chromatography [45,46]. In short, the sea gene was amplified by polymerase chain reaction (PCR) from S. aureus.…”
Section: Expression and Purification Of Seamentioning
confidence: 99%
“…Preparation of SEA toxin protein was completed by Escherichia coli expression system and Ni-NTA affinity chromatography [45,46]. In short, the sea gene was amplified by polymerase chain reaction (PCR) from S. aureus.…”
Section: Expression and Purification Of Seamentioning
confidence: 99%
“…Clostridium perfringens can lead to neurological lesions and enteritis in animals or humans (Uzal and Kelly 1998, Uzal et al 2002, Kiu and Hall 2018; Table ). It has been reported that high temperatures in summer can increase the occurrence of intestinal pathogen infections in animals (Li et al 2023). Therefore, we concluded that Przewalski's gazelles might be at risk of infection with potential pathogens and were more vulnerable to potential pathogens in summer.…”
Section: Discussionmentioning
confidence: 99%